Integral Ecclesiology: Resourcing the Church’s Future - Lennan, Richard (Theological studies, 2025)
Contemporary society’s political dynamics, especially the progressive-conservative divide, shape perceptions of the church and color perspectives on its future. Can ecclesiology provide a compelling alternative to political readings of the church, an alternative that is authentically theological, attentive to context, and conducive to realistic hope for the church’s future? To respond to that question, this article develops an “integral ecclesiology” that encompasses the implications that the church’s relationship to God has for its mission, engagement with history, ongoing conversion, and orientation to an eschatological fulfillment. The article concludes by briefly considering the Final Document of the Synod on Synodality (2021−24) as an expression of integral ecclesiology.